Bilingualism of Indonesian-English in Article Titles: A Case Study in Indonesian Mechanical Engineering Articles - Farahsani, Yashinta; Harmanto, Margaretha Dharmayanti (OKARA: Jurnal Bahasa dan Sastra, 2021)
Bilingualism happens not only orally but also in written Indonesian articles. Usually, the articles use Indonesian and English terms. Bilingualism even can be seen in the articlesâ€™ titles. One of the fields that often use bilingual terms is found in Mechanical Engineering’s articles. It happens because mechanical engineering has specialized terminology that sometimes untranslated into Indonesian terms. Many Indonesian experts have translated many English books with many variations of translation results. Therefore, the translation results are still questioned whether they are acceptable or not in Indonesian. This study aims to examine the factors of bilingualisms by observing titles of articles and finding the translation methods to translate the terminology from English to Indonesian. This study was qualitative research; by using questionnaires and observation, the research reveals that the main factor is untranslatability, where the English terminology cannot find its equivalent meaning in Indonesian. By using Molina and Albir’s translation techniques, researchers reveal that the English terminologies can be translated in Indonesian using (1) amplification, (2) borrowing, (3) established equivalence, (4) calque, and (5) literal translation. This study concludes that the untranslatability problem can be solved when the experts try to use the accepted translation results rather than using English terms.